2010
DOI: 10.1111/j.1365-2893.2009.01177.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant therapy used in conjunction with combination therapy for chronic hepatitis C improves sustained virus response rates in genotype 1 patients

Abstract: Combination treatment with pegylated interferon (Peg-IFN) and ribavirin remains the gold standard in the treatment of chronic hepatitis C. This therapy is limited by many side-effects including anaemia, neutropenia and reduced quality of life. The use of adjuvant agents to reduce the frequency of dose reductions because of haematological side-effects has been proven to be effective but there are few reports of what effect the use of these adjuvant therapies is having on sustained virological response (SVR). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Discussionsupporting
confidence: 61%
“…However, some studies have used decision analysis to estimate the cost-effectiveness of adjunctive therapy with erythropoietic growth factor (EGF) compared with that of standard care in the treatment of hepatitis C. The use of EGFs appears to be costeffective in patients with anaemia who are receiving combination therapy for HCV genotype 1, 2 or 3. Compared with The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Resultssupporting
confidence: 40%
See 2 more Smart Citations
“…From the data available, EPO itself exerts no additional antiviral activity, but the higher ribavirin doses tolerated with EPO administration may favour elimination of HCV. Indeed, four trials specifically assessed the rates of SVR between patients receiving PegIFN and ribavirin with and without EPO [21,46,47,49]. Shiffman et al.…”
Section: Clinical Studies On Use Of Epo In Chcmentioning
confidence: 99%